2016
DOI: 10.1002/ccd.26693
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of renal function in patients with aortic stenosis treated with transcatheter aortic valve replacement

Abstract: In this TAVR cohort, baseline GFR was the only independent predictor of AKI, which negatively impacted on 30-day and 1-year mortality. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
(47 reference statements)
1
7
0
Order By: Relevance
“…Similar to what has been reported in other TAVR cohorts, most of the AKI observed in this study was Stage 1 AKI [2, 10, 14, 2729]. However, even Stage 1 AKI is associated with increased mortality in ambulatory [8], non-cardiac surgery [7], cardiac surgery [30] and TAVR patients [27, 28]. Thus, it is important to identify risk factors that can potentially be modified to mitigate development of AKI after TAVR.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to what has been reported in other TAVR cohorts, most of the AKI observed in this study was Stage 1 AKI [2, 10, 14, 2729]. However, even Stage 1 AKI is associated with increased mortality in ambulatory [8], non-cardiac surgery [7], cardiac surgery [30] and TAVR patients [27, 28]. Thus, it is important to identify risk factors that can potentially be modified to mitigate development of AKI after TAVR.…”
Section: Discussionsupporting
confidence: 90%
“…Contrast dose did not associate with AKI in our cohort of TAVR patients. Contrast dose also did not associate with post-TAVR AKI in several other TAVR cohort studies [11, 14, 15, 19, 2729, 31, 32].…”
Section: Discussionmentioning
confidence: 75%
“…In the present issue of Catheterization and Cardiovascular Interventions , Meneguz‐Moreno et al evaluated the clinical variables related to changes in renal function following TAVR and the impact of AKI on outcomes . The authors were able to provide further evidence of an independent association between level of renal dysfunction before TAVR and incidence of AKI after implantation, which had been described previously in the literature .…”
mentioning
confidence: 54%
“…A study showed that there are a variety of factors linked with AKI following TAVR such as high preoperative creatinine levels, the need for blood transfusion, peripheral vascular disease, and hypertension and thus, the short term mortality (<30 days) in patients who developed AKI after TAVR and was higher compared to those without AKI [14]. Baseline glomerular filtration rate is an independent predictor of acute kidney injury in patients undergoing TAVR which adversely affects 30-day and one-year mortality [15]. A study found that male sex, left ventricular ejection fraction <30%, atrial fibrillation, and advanced chronic kidney disease were independently associated with higher mortality in patients receiving TAVR in predialysis or dialysis individuals [16].…”
Section: Discussionmentioning
confidence: 99%